Education and training of nurse teachers and managers with special regard to primary health care : report of a WHO expert committee, meeting held in Geneva from 3 to 7 October 1983 - World Health Organization; World Health Organization (WHO) Expert Committee (Geneva : World Health Organization, 1984)
Evaluates educational changes needed to equip nursing professionals to meet the changing health concepts implicit in primary health care. The report opens with a review of recent dramatic changes in the concept f health that have elevated the importance of nursing services and extended the responsibilities of nurses. Findings from a survey of educational and training facilities in 43 countries are then used to pinpoint several alarming inadequacies in present schools and programmes. Specific inadequacies are noted in the areas of administration, curriculum content and the mechanisms for its revision, procedures for student and programme evaluation, and discrepancies between an emphasis on technical competence and the real arts and skills required for community practice. The main sections of the report analyze the different steps necessary for a radical reorientation of training programmes. Of particular practical value is an assessment of the specific areas of competence that need to be developed in all educational programmes for post-basic training. The book concludes with examples of practical strategies used in two countries that have successfully integrated a primary health approach into training programmes for nursing personnel.
Keywords: Education and training of nurse teachers and managers with special regard to primary health care